Synthetic approach towards cephalezomine A and phomoidride D - Dong, Ping, author; Wood, John Louis, advisor; Williams, Robert M., committee member; Rovis, Tomislav, committee member; Bernstein, Elliot R., committee member; Partin, Kathryn M., committee member (Colorado State University. Libraries, 2011)
Two synthetic approaches towards cephalezomine A and phomoidride D are described separately. The first approach towards cephalezomine A invented a new method for the synthesis of 3-butoxy-1-chlorobutenone and successful constructed α-O and ß' -N disubstituted dienone for a designed key intermediate of cascade cyclization by Eschenmoser coupling of thiolactam and 3-butoxy-1-chlorobutenone. The second approach towards phomoidride D systematically studied the electronic effects of different ester substituents for the phenolic oxidation and inverse electron demand Diels-Alder reaction, which resulted in the synthesis of functionalized bicyclic [2.2.1] intermediate. Base on this, a new route for the synthesis of precursor of Grob fragmentation has been established towards the total synthesis of phomoidride D by samarium diiodide mediated radical cascade cyclization.
Keywords: Eschenmoser coupling; synthetic approach; samarium diiodide mediated radical cascade cyclization; phenolic oxidation and Diels-Alder reaction; phomoidride D; cephalezomine A